Blood in the sand : imperial fantasies, right-wing ambitions, and the erosion of American democracy - Bronner, Stephen Eric, 1949- (University Press of Kentucky, 2005)
Blood in the Sand is Stephen Eric Bronner's powerful critique of the current state of American foreign and domestic policy, ranging from the government's initial response to 9/11 and the assault on Afghanistan through the Iraqi War and the ramifications of the Israeli-Palestinian conflict. Bronner, who just months before the war began spent time in Iraq as part of a peace delegation, examines the state of twenty-first century America, a nation in which security against future terrorist attacks has become an obsession, "moral values" have turned into a slogan, and belief in the right to engage